Importance of family/social support and impact on adherence to diabetic therapy - Miller TA (Dove Medical Press, 2013)
Tricia A Miller, M Robin DiMatteoDepartment of Psychology, University of California, Riverside, Riverside, CA, USAAbstract: Diabetes mellitus affects 24 million individuals in the US. In order to manage their diabetes successfully, patients must adhere to treatment regimens that include dietary restrictions, physical activity goals, and self-monitoring of glucose levels. Numerous factors affect patients' ability to adhere properly, eg, self-efficacy, treatment expectations, health beliefs, and lack of social support. Consequently, diabetes management can be quite complex, requiring lifelong commitment and drastic changes to the patient's lifestyle. Empirical studies have shown positive and significant relationships between social support and treatment adherence among patients with diabetes. Social support from family provides patients with practical help and can buffer the stresses of living with illness. However, the exact mechanism by which social support affects patient adherence is not yet completely understood. Further research is needed to address how the differences in types of support, such as functional or emotional support, are linked to outcomes for patients. The purpose of this review is to summarize what is known of the impact of social and family support on treatment adherence in patients with diabetes and to explore the current methods and interventions used to facilitate family support for diabetic patients.Keywords: patient adherence, patient compliance, diabetes management, support, family, social